Karakteristik dan Derajat Keparahan Atrisi pada Narapidana Pengguna Sabu-Sabu (Methamphetamine) di Lembaga Pemasyarakatan Kelas IIA Kabupaten Jember - Nancy Amelia Rosa; Hestieyonini Hadnyanawati; Surartono Dwiatmoko (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2022)
Using methamphetamine has negative effects on oral health. The negative effect of methamphetamine use is bruxism which causes tooth attrition. It is able to cause masticatory disorders which affect the nutrient intake and reduce the quality of life. Methamphetamine prisoners in Prison Class IIA Jember who represent the methamphetamine users in Jember Regency are group of people who are susceptible to have tooth attrition because of their history using methamphetamine. This research aimed to determine the characteristics and description of severity degree of tooth attrition of methamphetamine prisoners in Prison Class IIA Jember. Methods: This is a description research which use cross sectional approach and was conducted in Prison Class IIA Jember in January 2020. We observed and interviewed 53 prisoners in Prison Class IIA Jember as respondent. Meanwhile, the attrition severity degree was examined by using the clinical judgement with benchmark of occlusal tooth wear index, while prisoners’ characteristics obtained from questionnaire analysis. Most of the respondents were male with the highest level of education is Senior high school, never attended Islamic school based, never get educated in Islamic boarding school, a frequency user with duration of drug use less than 1.5 years, using inhalation method, first experience using drugs in the late teens, unawareness of bruxism habit, experienced sensitive teeth, and keen to eat hard-textured food. The highest severe degree of attrition is moderate with a percentage of 43.4%. The inmates who use methamphetamine have several characteristics which may interfere health and lead to attrition.